Pedagogy of Social Studies Learning in Responding to Local, National and Global Inequalities - Nana Supriatna (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Pedagogy of Social Studies Learning in Responding to Local, National and Global Inequalities presented by Nana Supriatna